The Development And Validation Of The Maladies Of The Nafs Scale (MNS) - Ijaz, Shahid; Khalily, Muhammad Tahir; Al-Karam, Carrie York; Hallahan, Brian (Migration Letters, 2024)
This study aimed to create a reliable assessment tool, the "Maladies of Nafs Scale (MNS)," for measuring the impact of maladies of Nafs on an individual’s moral character and well-being in Islamic psychology.: The study employed a 200-item scale, iteratively refined through expert discussions. This scale, named the "Maladies of Nafs Scale (MNS)," was reduced to 108 items. Language experts reviewed it for clarity. The MNS was administered online to 355 students. Principal component analysis was used to identify underlying factors, and convergent validity was assessed by correlating it with related psychometric instruments. The Maladies of Nafs Scale (MNS) demonstrated strong reliability with a Cronbach’s α coefficient of 0.97. The analysis identified eleven distinct factors each with satisfactory reliability (Cronbach’s α ranging from 0.72 to 0.97). The Maladies of Nafs Scale (MNS) can serve as a valuable instrument for research in understanding and addressing maladies of Nafs. Furthermore, the MNS may find relevance in studies and interventi[1]ons focused on enhancing moral character and overall well-being within the context of Islamic psychology. The novelty of this study lies in the development of the Maladies of Nafs Scale (MNS), a robust and comprehensive tool designed explicitly for assessing maladies of Nafs within the context of Islamic psychology. The MNS not only fills a critical gap by providing a standardized assessment method but also opens doors for more profound and reliable research in this field, offering fresh insights into the relationship between moral character, well-being, and Islamic principles.